Efektivitas Penerapan Inquiry Teaching Model Terhadap Penilaian Tengah Semester Dalam Pembelajaran Pjok di SMP 4 Sejahtera Dramaga - Gumilang, Ryan Chandra; Ramadhan, Fajar; Dermawan, Dikdik Fauzi (Jurnal Ilmiah Wahana Pendidikan, 2024)
The Inquiry Teaching Model paradigm uses pre-experimental methods and techniques for learning. The heuristic strategy approach is a learning method that emphasizes student participation to encourage the development of critical thinking skills. Another description of the heuristic learning approach is that it is a series of activities designed to help students develop the habit of using analytical and critical thinking to solve problems. One approach to learning that uses issues as a means of "how to learn how" is the Inquiry Teaching paradigm. It is hypothesized that through fostering students' critical, reflective, and collaborative abilities, the Inquiry Teaching Model can enhance students' educational experience. The research data obtained is in the form of observational data in the learning process for each cycle. Observation sheet data is taken from observations of student actions in the learning process which are used to determine the process of applying the Inquiry Teaching Model model to improve the results of PJOK subjects. By using the PJOK learning daily assessment test instrument. Teachers assess the implementation of actions in order to improve PJOK learning outcomes during 6 meetings divided into 3 cycles. Furthermore, the data of these test results are divided into improvement cycles to determine the improvement of PJOK learning outcomes. The authors in this study processed and analyzed data based on the findings of the assessment of the effectiveness of the application of the Inquiry Teaching Model on midterm assessments in PJOK learning for junior high school students. In accordance with the author's objectives, this study uses quantitative research strategies, pre-experimental research methodology, and one-group pretest-posttest research design to determine the impact of the inquiry learning model on the results of the midterm exam at SMP 4 Sejahtera Dramaga. This model allows students to apply the concepts learned in practical contexts, such as in physical activity or sports. This helps students to understand the relevance of the subject matter to their daily lives. The Inquiry Teaching Model stimulates students' interest in learning independently. They are encouraged to explore topics more deeply, conduct their own research, and develop lifelong learning skills that they can apply outside the school environment.